A reconstruction method for restraining range walk error in photon counting Lidar via dual detection. (22nd March 2019) - Ye, Ling; Gu, Guohua; He, Weiji; Dai, Huidong; Mao, Tianyi; Chen, Qian
Abstract: The fluctuation of the intensity of echo-pulses introduces a range walk error (RWE) to a photon counting Lidar. In this paper, we present a reconstruction method without priori modeling to restrain the RWE and improve the ranging accuracy. The presented method is implemented by separating the echo-pulses into dual Geiger-mode avalanche photodiodes (Gm-APDs) then reconstructs the distribution of signal photoelectrons based on the Poisson probability response model. The presented method is theoretically analyzed by Monte Carlo simulation. The experimental results show that the RWE is reduced from −33.7 to −2.7 mm and depth precision is improved from 14.8 to 3.6 mm.